The Development of a Questionnaire on Factors Affecting Non Adherence Behavior among Indonesian Elderly Population - Andi Makkulawu; Adji Prayitno Setiadi; Tri Budi Wahyuni Rahardjo; Eko Setiawan (Universitas Indonesia, 2018)
Instruments which can be used to identify factors affecting the medication adherence of elderly with diabetes mellitus (DM) have not been discovered in Indonesia. The objective of this study was to develop a questionnaire to identify factors affecting elderly patients' medication adherence. The development of the questionnaire was conducted based on published references attained through the exploration of research evidence with several keywords and databases. Content validity and face validity test were conducted using experts' assessment. Construct validity test was conducted based on calculated R against table R while reliability test was conducted with Chronbach's Alpha. Present study produced a valid and reliable questionnairecomprising 35 questions in 14 subcategories from 4 factor domains with the calculated R = 0,357-0,788 andChronbach's Alpha = 0,934.The questionnairecan be used for further research throughout Indonesia, hence a complete overview of factors affecting elderly DM patients' medicine consumption adherencecan be obtained. The identification of factors related to the usage of DM patients' medicine is expected to serve as a base for the government, both of state and local government, to produce policies related to health interventions to be implemented.